# Trig

Verify the identity:
tanx(cos2x) = sin2x - tanx

Left Side = (sinx/cosx)(2cos^2 x -1)
=sinx(2cos^2 x - 1)/cosx

Right Side = 2sinx cosx - sinx/cosx
=(2sinxcos^2 x - sinx)/cosx
=sinx(2cos^2 x -1)/cosx
= L.S.

Q.E.D.

1. 👍
2. 👎
3. 👁

## Similar Questions

1. ### Math (Calculus AB)

For x≠0, the slope of the tangent to y=xcosx equals zero whenever: (a) tanx=-x (b) tanx=1/x (c) sinx=x (d) cosx=x Please help. I have a final tomorrow and I am working diligently to understand every type of problem that may show

2. ### Maths

If is a n acute angle and tanx=3 4 evaluate cosx-sinx cosx+sinx

Which of the following are identities? Check all that apply. (Points : 2) sin2x = 1 - cos2x sin2x - cos2x = 1 tan2x = 1 + sec2x cot2x = csc2x - 1 Question 4. 4. Which of the following equations are identities? Check all that

4. ### Math

How do I solve this? tan^2x= 2tanxsinx My work so far: tan^2x - 2tanxsinx=0 tanx(tanx - 2sinx)=0 Then the solutions are: TanX=0 and sinX/cosX = 2 sin X Divide through by sinX: we have to check this later to see if allowed (ie sinX

1. ### Trig.......

I need to prove that the following is true. Thanks (2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx) and thanks ........... check your typing. I tried 30º, the two sides are not equal, they differ by 1 oh , thank you Mr

2. ### pre-calculus

How do I prove that sinx/sinx+cosx=tanx/1+tanx

3. ### Math

1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 vibrations per second, write an equation in the form d=sinw(t) for the simple harmonic motion. 2) Verify the identity tan^2X-cot^2X/tanX+cotX=tanX-cotX I'm not

4. ### Trig Identities

Prove the following identities: 13. tan(x) + sec(x) = (cos(x)) / (1-sin(x)) *Sorry for any confusing parenthesis.* My work: I simplified the left side to a. ((sinx) / (cosx)) + (1 / cosx) , then b. (sinx + 1) / cosx = (cos(x)) /

1. ### Calculus

determine the absolute extreme values of the function f(x)=sinx-cosx+6 on the interval 0

2. ### trig

tanx = 5/12 and sinx

3. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 -

4. ### calculus

Verify the Identity: (Tanx + 1)/(secx + cscx) = sinx